2018
DOI: 10.1111/apha.13109
|View full text |Cite
|
Sign up to set email alerts
|

Regression of left ventricular hypertrophy provides an additive physiological benefit following treatment of aortic stenosis: Insights from serial coronary wave intensity analysis

Abstract: In aortic stenosis, both the outflow tract gradient and the presence of LVH impact significantly on coronary haemodynamics that cannot be appreciated by examining resting coronary flow rates alone. An immediate change in coronary wave intensity occurs following intervention with further effects appreciable with hypertrophy regression. The improvement in prognosis with treatment is likely to be attributable to both features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…15–17 Consequently, they do not necessarily reflect a steady-state pressure index after regression of LV hypertrophy. 12,18 For example, Broyd et al 14 demonstrated—using wave intensity analysis—that the amplitude of the backward decompression wave (the main driver of diastolic coronary flow) is reduced immediately after valve replacement but grows substantially at 6-month follow-up. Resting indices ought to be particularly prone to changes in cardiac workload and subtended mass following TAVI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15–17 Consequently, they do not necessarily reflect a steady-state pressure index after regression of LV hypertrophy. 12,18 For example, Broyd et al 14 demonstrated—using wave intensity analysis—that the amplitude of the backward decompression wave (the main driver of diastolic coronary flow) is reduced immediately after valve replacement but grows substantially at 6-month follow-up. Resting indices ought to be particularly prone to changes in cardiac workload and subtended mass following TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent a diagnostic coronary angiogram before TAVI. As the most rapid regression of LV hypertrophy occurs during the first 6 months after TAVI, [11][12][13][14] follow-up angiography was planned at that time point for reevaluation of FFR and RFR. To avoid confounding due to progression of coronary disease lesion anatomy (described below) was also reassessed at follow-up.…”
Section: Methods Study Design and Patient Populationmentioning
confidence: 99%
“…Wave intensity analysis is a rather specific art form that involves complicated looking formulas of differential equations. The authors conclude from their hemodynamic analysis that the hypertrophy regression contributes an additional benefit that might be part of an improvement in prognosis of this condition …”
mentioning
confidence: 93%
“…Aortic stenosis leads to left ventricular hypertrophy with potential further complications such as impaired coronary haemodynamics . The treatment of the stenosis might involve valve replacements.…”
mentioning
confidence: 99%